Deep distortions in everyday memory: Fact memory is illogical, too - Brainerd, Charles J; Bialer, Daniel M; Chang, Minyu; Liu, Xinya (Journal of experimental psychology. General, 2024)
A distinction has recently been drawn between surface distortions and deep distortions in false memory, where the former are conventional errors of commission and the latter are illogical relations among multiple memories of items. The deep distortions that have been studied to date are violations of the logical rules that govern incompatibility relations, such as additivity and countable additivity. Because that work is confined to laboratory word-list tasks, it is subject to the ecological validity criticism that memory for everyday facts may not exhibit such phenomena. We report evidence that memory for everyday facts displays the same deep distortions as laboratory tasks. We developed a version of the conjoint-recognition paradigm that measures memory for incompatible general knowledge facts, similar to those found on the quiz program Jeopardy! In experiments with university participants, four deep distortions were detected (violations of the additivity, countable additivity, universal set, and compensation rules), with participants consistently remembering more than what is logically possible. The distortions were more robust than in laboratory experiments, and memories of incompatible facts (e.g., Jupiter and Saturn cannot both be the largest planet in the solar system) did not suppress each other. These patterns were replicated in subsequent experiments with older and more diverse participant samples. Consistent with the notion that deep distortions are by-products of gist memory, conjoint-recognition modeling analyses revealed that memory for everyday facts was even more reliant on gist than memory for word lists, and that verbatim memory was near-floor. (PsycInfo Database Record (c) 2024 APA, all rights reserved).